Administrative empowerment and its impact on customer satisfaction (An applied study on customer service employees in private companies in the Asir region- Saudi Arabia) - Alariki, Basem Qaid (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of the research was to determine the level of administrative empowerment among customer service employees and the level of customer satisfaction, and to determine the relationship and impact between the dimensions of administrative empowerment and customer satisfaction, and the researcher used the descriptive approach using the questionnaire tool to collect data on a sample of 87 individual workers working in customer service in the private sector in an area Aseer, and the researcher concluded several results, the most important of which were: that there is a high application for administrative empowerment of customer service employees in private companies in the Asir region with a general average of (4,135) and in an acceptable general direction, and there is a high level of customer satisfaction with private companies in the Asir region from the point of view of employees Customer service, with a general average of (3.80) and in an acceptable direction, and a strong correlation between the dimensions of administrative empowerment represented by (delegation of powers- participation in decision- making- work teams- training and education- independence- motivation) combined and customer satisfaction, with the Pearson correlation coefficient Its value was (0.77) at the level of significance (0.05), and the study also concluded that the dimensions of administrative empowerment combined affect the customer satisfaction by (60%), and that all dimensions of administrative empowerment affect significantly the satisfaction of customers with the exception of the delegation of powers and after participation in taking the decision.Finally, the researcher recommended private companies in the Asir region to pay attention and focus on increasing delegation of powers and the participation of customer service employees in making administrative decisions as the dimensions of administrative empowerment.
Keywords: Administrative empowerment; Customer satisfaction; Delegation of authority; Participation in decision-making; Work teams; Training and Education